The Analysis of Experiential Learning Method of Dale's Cone Experience Model in Improving the Effectiveness of Arabic Language Learning - Cecep Sobar Rochmat Cecep; Amalia Nur Afasa Amalia; Abdul Hafidz bin Zaid Abdul Hafidz; Moh Alwi Yusron Alwi; Sania Karimah Liputo Sania (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This study purposed to analyze the effectiveness of the Arabic language learning model based on Edgar Dale's cone of experience theory. The method used library research by taking books, journals, and documents. The result of this research is that Arabic language learning with an experiential learning model, according to Edgar Dale's cone of experience, is effective learning and can help to develop Arabic language learning that is focused and empowers students to master it. Learning Arabic through this model is also very effective for teaching Arabic as a means of communication. Experiential learning and Edgar Dale's cone of experience theory have a strong fit in the context of Arabic language learning. Dale's cone of experience theory illustrates different levels of student participation and involvement in learning, ranging from concrete experience to abstract conceptualization. According to Dale, direct and interactive experiences promote more effective learning, which is consistent with the experiential learning approach. In experiential Arabic learning, students engage in direct experience by speaking, listening, reading and writing in Arabic, which is the first step in the cone of experience.